(untitled) (Research, Society and Development, 2021)
The objective was to evaluate the nutritional profile of the medical students of the Community University of the Region of Chapecó (Unochapecó) regarding the consumption of fast foods. This is a quantitative qualitative cross-sectional study, through a questionnaire formulated in the Google Forms platform, applied to the students of Medicine of the Unochapecó, between March, 2019. The data obtained were organized in a spreadsheet in the Microsoft Office Excel 2016 system and PAST, version 3.26, to analyze the position and dispersion measures, with the help of graphs and tables. The sample had a n=50, with a mean age of 21.6 years, average weight of 62.4 kg and BMI of 21.9 kg/m², with the majority participation of students from the 3rd semester. The highest frequency of fast food consumption was twice a month (32%), and the most ingested foods were pizza and chips. There is a greater preference for fast foods due to its speed, practicality and good taste. There is a need for diversified food options in universities, focusing on healthy foods, as a form of prevention of chronic non-communicable diseases (NCDs), reducing public spending on medicines, hospitalizations and surgeries.